Effect of Expressive Arts Therapy on Aggression and Trauma among Women Deprived of Liberty - Buenaflor, Venise T.; Capay, Abigaile Rose Mary R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study investigated the effect of an Expressive Arts Therapy-based intervention program on trauma and aggression symptoms of women deprived of liberty (WDL). Using a multiple-group pretest-posttest design, 45 WDL (Mean age = 37.3) were matched based on age, nature of incarceration, and months of facility detention, then randomly assigned to a performing arts experimental group (n=15), a visual arts experimental group (n=15), or a waitlist control group (n=15). Data were analyzed using paired samples t-tests, one-way ANOVA, Tukey’s post-hoc test, and Cohen’s d for effect sizes. Results showed that the EAT-based intervention significantly reduced aggression symptoms in both the visual arts group (t (14) = 2.24, p = .042, d = .579), as well as the performing arts group (t (14)=2.39, p=0.032, d=.616), both with medium effect sizes. However, one-way ANOVA comparing posttest scores across groups did not reveal statistically significant differences (p > .05), suggesting that while EAT-based interventions may be effective at an individual level, no single modality was significantly more beneficial than another. Future research should explore long-term effects, moderating variables, and therapy intensity to better understand the impact of expressive arts interventions for incarcerated women.